Akulturasi Musik Gembrung Sebagai Media Komunikasi Islam - Muchlis Daroini; Kayyis Fithri Ajhuri (Academic Journal of Da'wa and Communication, 2022)
Gembrung music is a traditional Islamic art that has developed a lot in Java. Its existence indicates a da'wah process in order to convey the messages of Islamic teachings in Java. The intersection of Muslim and Javanese groups creates a form of cultural acculturation, each of which represents two acculturated cultures. By using a qualitative methodology, the research focus is on literature and gembrung in Java, the aim of this study is to find the process of acculturation of the traditional Gembrung musical instrument. Where in Gembrung art it is found as a communication tool in preaching as well as a process of acculturation of music. Among them, several elements of gembrung music adopted Javanese music, including kenong and gong which were replaced with tambourines, which are musical instruments made of wood and goat skin. In addition to the form of abolition or omission, there is also musical pluralism, where one musical instrument can be accepted by another group but still places one musical instrument that represents each acculturation group. Among those that must still be included are drums as a representation of Java, and also tambourines as a representation of Islam-Arabism. What's interesting is that each musical instrument which is a cultural representation becomes the central determinant of other musical elements. The acculturation of this musical element has led to cultural acceptance by the Javanese people of the Gembrung art. Likewise, there is acceptance of Muslim groups as a representation of Islamic music.